Pengaruh Kenaikan Harga Bahan Baku Terhadap Keuntungan Penjualan Sate dengan Metode Korelasi Analysis - Ari Andriyus Puji; Denur Denur; Hendri Ali Ardi; Dimas Haritz (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
The culinary industry is an industry that is in great demand, one of which is the satay business. The problem that occurs is the increase in raw material prices which results in a lack of profit for satay traders. From this background, the researcher wanted to know the effect of the increase in the price of satay raw materials on the profits. Of the various types of raw materials, researchers took 6 main ingredients as a reference for price increases. The data was taken by observation to the management and library data, then analyzed quantitatively. The results of the analysis show that the most influential raw material is chicken meat.